2016
DOI: 10.1111/his.12922
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia‐related proteins in invasion of ameloblastoma cells: crosstalk between NOTCH1, hypoxia‐inducible factor 1α, a disintegrin and metalloproteinase 12, and heparin‐binding epidermal growth factor

Abstract: AME showed an increased presence of proteins associated with tumour invasiveness, which indicates a possible role of these proteins in the biological behaviour of this tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…In this study, odontogenic cysts showed the highest immunoexpression of HIF-, suggesting that these lesions undergo to restricted oxygen supply. Ameloblastoma samples also showed increased expression of HIFin solid areas of epithelial islands, supporting the idea of localized intratumoral hypoxia [24].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In this study, odontogenic cysts showed the highest immunoexpression of HIF-, suggesting that these lesions undergo to restricted oxygen supply. Ameloblastoma samples also showed increased expression of HIFin solid areas of epithelial islands, supporting the idea of localized intratumoral hypoxia [24].…”
Section: Discussionsupporting
confidence: 60%
“…Proliferation of the epithelium and apoptosis are fundamental events in cystogenesis [12,22] and have been related to the development of odontogenic cysts and tumors [15,23]. Hypoxia has already been associated with cyst formation in ameloblastoma [24].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report that clearly links HB-EGF-EGFR signaling to the angiogenic switch of the MGUS-to-MM transition. So far, enhancement of HB-EGF expression in carcinogenesis has only been found in solid tumors under hypoxic conditions [29][30][31][32]. As shown in ameloblastoma, transcription and post-transcription factors such as hypoxia-inducible factor 1α (HIF-1α), ADAM-12, and NOTCH1 are directly involved in an HB-EGF autocrine amplification loop and facilitate local tumor invasiveness [29].…”
Section: Discussionmentioning
confidence: 99%
“…Its activation plays an essential role in the invasive process, being fundamental for tumour growth and aggressiveness, with overexpression observed in many human tumours 4 , 36 38 . Immunohistochemistry studies have observed the overexpression of HIF-1α in AME and have discovered that this is associated with its aggressive biological behaviour 17 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Some of these proteins have already been studied in AME, COC and DF. Three studies verified the expression of HIF-1 α and found a higher expression of this protein in AME when compared to COC and DF, and suggested that may be associated with its aggressive biological behaviour [17][18][19] . Three studies have verified the expression of VEGF and found a higher expression of this protein in AME when compared to odontogenic keratocyst, dentigerous cyst or tooth germ, suggesting that the up-regulation of this protein in AME might be associated with neoplastic or malignant changes of odontogenic epithelial cells [20][21][22] .…”
mentioning
confidence: 89%